Мимолетности, или Подумаешь, бином Ньютона! - Вильмонт Екатерина Николаевна (Про жизнь и про любовь: Екатерина Вильмонт, 2016)
Экземпляры: ф. 15 (20190312) / Инвентарный номер: 56803 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6